The Muhammadiyah and the Theory of Maqasid al-Shari'ah - Jamil, Fathurrahman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
Muhammadiyah is an organizational and socio-religious movements in Indonesia related to the reform (tajdid) Islam in general and Islamic law in particular. For Muhammadiyah, tajdid has a double meaning: the reform and modernization. To run tajdid correctly, according to the Muhammadiyah need to use the power of the mind in accordance with ijtihad. Muhammadiyah view that ijtihad can be done on the issues that have not been defined by the Qur'an and Sunnah explicitly and also to the problems that have been defined by these two sources.DOI:Â 10.15408/sdi.v2i1.841